Relationship between sleep disorders and the prognosis of neurological function after stroke - Zhang, Yajing; Xia, Xiaoshuang; Zhang, Ting; Zhang, Chao; Liu, Ran; Yang, Yun; Liu, Shuling; Li, Xin; Yue, Wei (Frontiers in Neurology, 2022)
Objective This study aims to investigate the effects of sleep disorders on the prognosis of neurological function after stroke and other factors affecting the prognosis after stroke. Method We designed a cohort study. A total of 1,542 patients with their first stroke were hospitalized in the department of neurology of Tianjin Huanhu Hospital from 2015.6.1 to 2016.12.31. We recorded the personal histories of patients. The MMSE (mini-mental state examination), MoCA (Montreal Cognitive Assessment), HAMD (Hamilton Depression Scale), National Institutes of Health Stroke Scale (NIHSS) score, mRS (Modified Rankin Scale), BI (Barthel Index), PSQI (Pittsburgh Sleep Quality Index), ESS (Epworth Sleepiness Scale), Berlin questionnaire, and nocturnal TST (Total sleep time) were assessed before discharge, 3 months, 6 months, and 4 years (2019–2020) after stroke. Result Low sleep quality (OR 2.019, 95%CI 1.199–3.398, p = 0.008), nocturnal TST (<7 h) (OR 4.060, 95%CI 1.494–11.034, p = 0.006), nocturnal TST (>8 h) (OR 5.928, 95% CI 2.134–16.464, p = 0.001) were risk factors for poor neurological function recovery at 3 months after stroke. Nocturnal TST (<7 h) (OR 13.042, 95%-CI 2.576–66.027, p = 0.002) and nocturnal TST (>8 h) (OR 11.559, 95%-CI 2.108–63.390, p = 0.005) were risk factors for poor neurological function at 6 months after stroke. Nocturnal TST (<7 h) (OR 2.668, 95% CI 1.250–5.698, p = 0.011) and nocturnal TST (>8 h) (OR 2.516, 95% CI 1.080–5.861, p = 0.033) were risk factors for poor neurological function at 4 years after stroke. High risk of OSA (HR 1.582, 95%CI 1.244–2.012, p < 0.001) was a risk factor for all-cause death in patients followed up for 4 years after stroke. Conclusion Low sleep quality is associated with short-term poor neurological function after stroke. Unusual nocturnal TST (long or short) is associated with short-term or long-term poor neurological function after stroke. A high risk of OSA is associated with a higher risk of all-cause death after stroke.